Online Multiple Service System For Home User - Kok, Jin Peng (2002)

(untitled)
The aim of this project is to develop an online multiple service system for the home users. The home users may choose the services they need easily through this interactive online system. The few problems encountered by the services sector are hindering its' future development. The revolution of Information Technology and Communication that has contributed to the e-commerce should help the services sector to solve these problems. The e-commerce should not only allow consumers shop on the web through the Internet online system, consumers should also have the opportunity to choose the services they need conveniently. The interactive online system that operates 24 hours a day helps the services sector expands the market; generate a closer relationship between the suppliers and the consumers. Meanwhle the online system also improves the company's ability to manage the information inside the company more effectively. The methodology choosen to develop this online system involving four phases. These four phases are system analysis, system design, system development and the system testing. System analysis is the process of gathering and analysing the information. System design decides the way to build the new system. Programming language like Active Server Pages (ASP), VBScript, JavaScript, Structure Query Language (SQL) and HyperText Markup Language (HTML), and the sohare like Microsoft Visual InterDev, Macromedia Dreamweaver, Microsoft Structure Query Language (SQL), Adobe Photoshop dan Coffee Cup GIF Animator use to develop the system in the system development phase. Finally the system is tested in the system-testing phase before the implementation.